Buzzati's Miracles between writing and painting - Roberta Coglitore (Between, 2012)
The analysis of double work I Miracoli di Valmorel by Dino Buzzati, understood as the best outcome of his pictorial and literary production, allowed a reflection on the expressive and combinatory possibilities of visual and verbal texts and on the negotiation of borders between the two media.